(untitled) (Andamios, Revista de Investigación Social, 2008)
The purpose of this essay is to expose an area of speculation, which is necessary for the social communication investigator’s understanding and investigation of phenomena as historical fact. Therefore, we attempt to describe a part of German philosophy of history, to explain the usefulness of its language, categories and relationships, as a theoretical tool in the analytical and interpretive of a communications scholar, for the sake of being able to determine the historic process of communication, the latter understood as a manifestation of a culture semiotics.